SIFAT KAYU LAPIS PINUS DENGAN BEBERAPA MACAM KETEBALAN - Suwandi Kliwon; M I Iskandar; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Experimental plywood panels were made from bolts of tapped and untapped Pinus merkusii trees obtained from East Java. The bolts were rotary peeled into veneers of 1.5 mm, 2.0 mm and 3.0 mm thick. Veneer of 1.5 mm was exclusively used as face veneer and others for core. Plywood panels were glued with urea formaldehyde resin. Plywood were made with 5 thickness variation (5.00 mm, 6.00 mm, 7.5 mm, 9.0 mm and 12.00 mm). The physical and mechanical properties of all panels were tested according to the ASTM standard, and bonding strength of plywood was tested according to Indonesian, Japanese (JAS) and Germany (DIN) standards. The results indicated that there is no significant difference in moisture content, density of plywood made tapped and untapped pine wood. Mechanical properties of plywood (bending strength, tensile strength and compression strength) were significant difference made of tapped and untapped pine wood also vice versa with its thickness variation.Bonding of glue of plywood there is no significant difference made tapped and untapped pine wood. Only plywood which tested its bonding strength using Germany standard indicated significant shear strength of plywood with thick ness 5.00 mm is better than that of the 6.00 mm thickness.Modulus of rupture and compression strength of tapped pine plywood are better than the untapped one.